2019
DOI: 10.1590/0101-35172019-2854
|View full text |Cite
|
Sign up to set email alerts
|

War and international trade: Impact of trade disruption on international trade patterns and economic development

Abstract: The disruptions of trade flows due to military conflicts leads to changes in economic structures of countries, to the subsequent changes in trade policies, and to the changes of established trade patterns with impact on position of countries in international trade system. This paper deals with three modern time’s conflicts: Napoleonic Wars, WWI and WWII. We argue that the changes resulting from the disruption of trade flows itself, leads to changes and shifts which are relatively permanent, independent on outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 15 publications
1
8
1
1
Order By: Relevance
“…This supports the argument of the school of thought that says nations/communities that trade with each other find conflicts and hostilities between each other unattractive and costly, thereby reducing the probabilities of engaging each other in violent conflict. This finding is also consistent with the empirical findings of Martin et al (2012), Seitz et al (2015), Polachek (1980), Chang et al (2004), Krpec and Hodulak (2019), Paganelli and Schumacher (2019), and Garfinkel and Syropoulos (2015). They found that countries with greater trade engage in the least amount of hostilities.…”
Section: Trade and Internal Conflict In Nigeriasupporting
confidence: 91%
See 1 more Smart Citation
“…This supports the argument of the school of thought that says nations/communities that trade with each other find conflicts and hostilities between each other unattractive and costly, thereby reducing the probabilities of engaging each other in violent conflict. This finding is also consistent with the empirical findings of Martin et al (2012), Seitz et al (2015), Polachek (1980), Chang et al (2004), Krpec and Hodulak (2019), Paganelli and Schumacher (2019), and Garfinkel and Syropoulos (2015). They found that countries with greater trade engage in the least amount of hostilities.…”
Section: Trade and Internal Conflict In Nigeriasupporting
confidence: 91%
“…For many authors in the liberalist school, trade symbolizes a pathway to peace and prosperity, as argued by the liberalists (Polachek, 1980;Barbieri, 1996;Cali, 2015, Tanious, 2019Krpec and Hodulak, 2019;Su et al, 2020;Lee and Pyun, 2009). Polachek (1980) provided evidence supporting the hypothesis that nations that experience a high level of INT-TRAD possess more incentives to keep healthy relationships with their trade partners.…”
Section: Evidence From the Literaturementioning
confidence: 90%
“…The Russian economy, having certain advantages, still faced a number of difficulties. Given the imposition of sanctions on food imports, combined with the fall in oil prices and the weakening of the Russian ruble as the official currency, the Russian economy has received quite high inflation, that is, the overall rise in prices [16][17][18][19][20][21][22]. This is also seen in figure 2 below; it was from the beginning of the first sanctions in early 2014 that there was a slight increase in inflation, but after Russia introduced counter-sanctions to ban the import of certain types of food -it is obvious that this caused serious market turmoil and a significant increase in inflation, which amounted to 16% in March 2015 [23].…”
Section: Methodsmentioning
confidence: 99%
“…Arguably, the chasm between national policy was significantly smaller in the dawn of the New York Convention, allowing for relative consensus to be achieved in its text, while irreconcilable points, such as the definition of arbitral awards, were left untouched (Gaillard, 2009). Further, the decade of the drafting of the Convention was marked by states' collective efforts and to reinforce trade in light of ceasing and preventing the reignition of war (Krpec and Hodulak, 2019;McDonald, 2004;Sutton, 1967). Having experienced the consequences of World War II (WWII) on national economies, political leaders could have been relatively flexible with concessions at the drafting stage of the New York Convention, which was marked by an era of multi-state cooperation on numerous international trade law conventions (Garcia et al, 2015).…”
Section: Diverging Idiosyncrasiesmentioning
confidence: 99%